PENERAPAN PEMBERIAN PERMEN KARET XYLITOL UNTUK XEROSTOMIA PADA PASIEN PENYAKIT GINJAL KRONIS DI RUMAH SAKIT TK. III 04.06.02 BHAKTI WIRA TAMTAMA SEMARANG - Ainnur Rahmanti; Kukuh Raharjo (Jurnal Kesehatan Medika Udayana, 2018)
Hemodialysis is an action used in kidney failure patients to remove and clean up metabolic waste substances and other toxic substances. So you have to undergo hemodialysispatients undergoing hemodialysis must be limited to administration of fluids. The consequences of fluid restriction can lead to complaints of thirst and xerostomia. Giving xylitol gum can stimulate saliva to overcome xerostomia. The purpose of this case study is to describe the application of xylitol gum to reduce xerostomia in patients. The method used in this study is Quasy Experiment. The instrument used was SXI-D (Summated Xersotomia Inventory-Dutch Version). Subjects of 2 people over the age of 30 years. The intervention was done in the form of chewing 2 grains of xylitol gum 3 times a day after a large meal and brushing his teeth for 2 consecutive weeks. The results of case studies on subject 1 showed a decrease in xerostomia before being given the first hemodialysis measurement intervention, namely 23 severe xerostomia, on the last day of intervention, 7 mild xerostomia. In subject 2 there was a decrease in xerostomia before the first. gum administration is recommended as a nursing intervention in the management of patients with hemodialysis measurement intervention was given, 23 severe xerostomia, on the last day of intervention, 10 mild xerostomia. The application of xylitol xerostomia.